The sweet side of wound healing: galectins as promising therapeutic targets in hemostasis, inflammation, proliferation, and maturation/remodeling - Čoma, Matúš; Manning, Joachim C; Kaltner, Herbert; Gál, Peter (Expert opinion on therapeutic targets, 2023)
INTRODUCTION: Understanding the molecular and cellular processes involved in skin wound healing may pave the way for the development of innovative approaches to transforming the identified natural effectors into therapeutic tools. Based on the extensive involvement of the ga(lactoside-binding)lectin family in (patho)physiological processes, it has been well established that galectins are involved in a wide range of cell-cell and cell-matrix interactions. AREAS COVERED: In the present paper, we provide an overview of the biological role of galectins in repair and regeneration, focusing on four main phases (hemostasis, inflammation, proliferation, and maturation/remodeling) of skin repair using basic wound models (open excision vs. sutured incision). EXPERT OPINION: The reported data make a strong case for directing further efforts to treat excisional and incisional wounds differently. Functions of galectins essentially result from their modular presentation. In fact, Gal-1 seems to play a role in the early phases of healing (anti-inflammatory) and wound contraction, Gal-3 accelerates re-epithelization and increases tensile strength (scar inductor). Galectins have also become subject of redesigning by engineering to optimize the activity. Clinically relevant, these new tools derived from the carbohydrate recognition domain platform may also prove helpful for other purposes, such as potent antibacterial agglutinins and opsonins.
Keywords: galektiny; hemostáza; Cell Proliferation; Wound Healing; Inflammation; Hemostasis; hojení ran; proliferace buněk; Galectins; Humans; lidé; zánět